ANALISIS PERBANDINGAN THROUGHPUT PADA GENERAL PACKET RADIO SERVICE (GPRS) DAN ENHANCED DATA RATE FOR GSM EVOLUTION (EDGE) - Ningsih, Yuli Kurnia; Agoes, Suhartati; Sampekalo, Winer (Jurnal Teknik Elektro, 2007)
The Presence of Enhanced Data rate for GSM Evolution (EDGE) to give new solution inhigh speed transfer. EDGE technology prepared for service data and prepare to widebandwitdh service. Throughput is one of kind way to measured network condition of GPRSand EDGE. Throughput is total time that needed to send data so that we know the velocityfrom data transmission of GPRS and EDGE. This paper is presence of throughput betweenexcessting network GPRS system and EDGE. Analysis result, EDGE Throughput almost 3times of GPRS throughputKeyword: Enhanced Data rate for Global Evolution (EDGE), General Packet Radio Service(GPRS), throughput